Regional demand for water in Greece using panel data - Πανάς Επαμεινώνδας Ε. (SPOUDAI Journal of Economics and Business, 2002)
Regional water demand is estimated as a function of water price, household size, income, and temperature using cross-section and time-series data from 29 regions in Greece, between 1995-1998. The data are panel data and the Hausman test indicates that the fixed effects model cannot be rejected in favour of the random effects model and so the former becomes the analytical model of choice. Estimated demand was found to be highly responsive to changes in water price, income and the level of the climatic variable. JEL: classification C23, H70, Q25